Motherhood Wage Discrimination, Evidences from Korean Labor and Income Panel Study (KLIPS) 1998-2017, South Korea - Choi, Seulki; Mingean Park (KDI School of Public Policy and Management, 2019)
This study uses the KLIPS data between 1998 to 2017 to examine whether wage discrimination between mothers and non-mothers exists in the South Korea labor market. We compare the amount of wage gap from OLS model to a variety of Fixed effect models which have different types of productivity measures. The results show that mothers are discriminated against in the labor market. Interestingly, the amount of discrimination is bigger for highly-educated women than less-educated women. Especially the semi-professional workers who have the educational attainment level at college degree or higher are the most serious victim of the motherhood wage discrimination.
Keywords: Gender Wage Gap; Motherhood Wage Discrimination; Motherhood Wage Penalty